Description of an experience to improve technological competence in a transverse way in the education of pre-service teachers. - Raúl Tárraga Mínguez; M. Inmaculada Fernández Andrés; Gemma Pastor Cerezuela; Carla Colomer Diago (Universitat Politècnica de València, 2013)
The acquisition of a technological competence that can enable the use of ICT as an educational tool is one of the goals of the initial training of future teachers. However, in this initial training there are few subjects that are directed specifically to analyze how to use ICT as an educational tool, so that this item should be treated on a transverse way during all the subjects of these studies. This work describes an experience in which different activities are implemented and educational materials are used to aim the development of technological competence in students of the degrees in primary education teacher and child teacher from the subject of Special Educational Needs in the University of Valencia. These activities and materials are not directly related to the content of the subject, but serve as means of support for the approach of the own content of the subject. Among the strategies used to develop this technological competence are included: employment during classes of an interactive whiteboard, creating websites and blogs related to the course content, the design of digital concept maps that reflect graphically the contents studied, creating interactive pósters that address the content studied, or the design of computerized educational activities adressed to students with special education needs.